Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2003)
Table of Content Amelie von Wulffen – Bruchstücke by Philipp Kaiser Francis Alÿs Portrait Francis Alÿs by Kitty Scott One More Step by Saul Anton Strange Attractor by Robert Storr Isa Genzken Three Decades, a Reconstruction by Jörg Heiser The Skyscraper at Ear Level by Pamela M. Lee Fragility can be a very beautiful thing by Michael Krajewski & Isa Genzken Anish Kapoor Kapoor’s Vertigo by Norman Bryson A Word in the Giant’s Ear by Kurt W. Forster The Perforate Self, or Nought Is Not Nought by Marina Warner Robert Crumb, Insert Capitalist Neo-Realism – Swetlana Heger by Stuart Comer Inquiry: The Economy of Attention I Do This, I Do That, The Peronality Artist and Heavy Metal Dandyism, Cumulus from America by Jesse Pearson A Future One Would Like to Be Able to Defer, Cumulus from Europe by Eric Troncy Sunset Boulevard, Rodney Graham’s Rheinmetall/Victoria-8 by Sergio Risaliti
﻿The three idiosyncratic positions presented in this issue of Parkett share common ground: they all boldly frustrate and invert received notions of space. Francis Alys achieves these objectives quite simply by strolling through a metropolitan area like Mexico City. The way he does this, how he talks about it and reports on it invests not only the figure of the artist but also the concept of an artwork with the flavor of being on the road, which in turn blurs positionings like center and margin (as analyzed by Saul Anton). In his Edition for Parkett, Alys has created a tin dog filled with magnets, a “Ghetto Collector,” thereby inviting our readers to take walks that will yield a highly visible added value—in suitable surroundings—inasmuch as the wheeled creature attracts all the stray metal lying around on the streets. The artist has also joined forces with others in the attempt to move the proverbial mountain, and has used the Museum of Modern Art’s temporary move to Queens as an excuse to organize a very real procession of masterworks, of profane “sacred images.” (editorial by publisher)
boek
Keywords: Alÿs, Francis; Kapoor, Anish; Genzken, Isa